Between bodies: Animality and vulnerability in La mosquitera (2010) by Agustí Vila. Issue 2 (June 2019) - Marcer, Elisenda
Abstract : This article sets out to situate the 2010 Catalan film La mosquitera (2010 ) ['The Mosquito Net'] by Agustí Vila within the context of the strand of European cinema that has addressed animality as an element of philosophical, ontological, and aesthetic reflection. I argue that the film's engagement with the borders between the animal and the human, and overt representation of the intermingling between animal and human bodies, forces the spectator to rethink the limits of dominant anthropocentric perspectives on literary and visual texts. Drawing on contemporary scholarship in the field of animal studies and placing it in dialogue with André Bazin's reconceptualization of the material ontology of film, I analyse questions of materiality and vulnerability in Vila's film by considering aesthetic and ethical relations as well as the responses that these elicit from the spectator.